Polypeptides Micelles Composed of Methoxy-Poly(Ethylene Glycol)-Poly(l-Glutamic Acid)-Poly(l-Phenylalanine) Triblock Polymer for Sustained Drug Delivery - Xingzheng Liu; Rongrong Fan; Boting Lu; Yuan Le (MDPI AG, 2018)
Methoxy-poly(ethylene glycol)-poly(l-glutamic acid)-poly(l-phenylalanine) triblock polymers with different architecture were synthesized as drug carrier to obtain sustained and controlled release by tuning the composition. These triblock polymers were prepared by ring opening polymerization and poly(ethylene glycol) was used as an initiator. Polymerization was confirmed by 1H NMR, FT-IR and gel penetration chromatography. The polymers can self-assemble to form micelles in aqueous medium and their critical micelle concentrations values were examined. The micelles were spherical shape with size of 50⁻100 nm and especially can arranged in a regular manner. Sorafenib was selected as the model drug and the drug loading performance was dependent on the composition of the block copolymer. In vitro drug release indicated that the polymers can realize controlled and sustained drug release. Furthermore, in vitro cytotoxicity assay showed that the polymers were biocompatible and the drug-loaded micelles can increase toxicity towards tumor cells. Confocal fluorescence microscopy assays illustrated that the micelles can be uptaken quickly and release drug persistently to inhibit tumor cell growth.